O papel da interatividade nas transformações da sociabilidade - Voltolini, Anyzaura Vieira (2014)
Technological advances enabled by digital media introduced as new magna the interactivity in contemporary communicative process. Instrumental in verbal conversation, interactivity had disappeared from other media, now reappearing in network communication with unusual characteristics. This project is based on studying the changes that interactivity is bringing for the socialization process from the deepening due to multiple aspects of the issue of interactivity in digital media. The concept of sociability was studied based on the work of Simmel, according to us an anticipator of the significant questions created because of social networks. Theoretical analysis undertaken by Muniz Sodré (2010) and Alex Primo (2007) introduced a new communicative process with its basis in the interaction, when the new technological resources greatly affect the behavior of the interactors, subject that will be discussed according to the daily ethos virtualization of Lévy, beyond his considerations of hipercorpo, depopulation and dispossession. According to these and other theorists, this research discusses the current reflexivity and communicational processes, or, those which are able of providing an interactional, circular, aneous and immediately with a constant meaningful of tradicional concepts and principles of the relation between emission and reception. Interactivity has become a major focus on informational communicative development, bringing new habits, customs and values, transgressing limits and stimulating the transformation of sociability. This is the hypothesis we will work on the methodology will collate the theoretical concepts with the observation of interactive behavior taking place on blogs and social networks